2003
DOI: 10.1115/1.1564069
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Constraint-Modified J-R Curves for Carbon Steel Storage Tanks

Abstract: Mechanical testing of A285 carbon steel, a storage tank material, was performed to develop fracture properties based on the constraint theory of fracture mechanics. A series of single edge-notched bend (SENB) specimen designs with various levels of crack tip constraint were used. The variation of crack tip constraint was achieved by changing the ratio of the initial crack length to the specimen depth. The test data show that the J-R curves are specimen-design-dependent, which is known as the constraint effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…Garwood [225] was among the first and showed that an experimental J-R curve derived from the center-cracked panel was appreciably steeper than one obtained from a three-point bend specimen, but the initiation toughness values were essentially identical for these two geometries. Similar constraint effects on J-R curves for ductile materials under plane strain conditions were observed widely by many other investigators, including McCabe et al [226], Towers and Garwood [227], Eisele et al [228], Hancock et al [229], Joyce et al [230][231][232], Wardle [233], Lam et al [234], Neimitz et al [235], and Shen et al [236]. All experimental results showed that deeply cracked, bending loaded standard specimens result in lower J-R curves, and shallow cracked, predominantly tensile loaded nonstandard specimens lead to higher J-R curves, with the plane strain initiation toughness J Ic being nearly independent of these specimen geometry and loading mode effects.…”
Section: Experimental Observations On Fracture Constraint Effectsupporting
confidence: 54%
See 2 more Smart Citations
“…Garwood [225] was among the first and showed that an experimental J-R curve derived from the center-cracked panel was appreciably steeper than one obtained from a three-point bend specimen, but the initiation toughness values were essentially identical for these two geometries. Similar constraint effects on J-R curves for ductile materials under plane strain conditions were observed widely by many other investigators, including McCabe et al [226], Towers and Garwood [227], Eisele et al [228], Hancock et al [229], Joyce et al [230][231][232], Wardle [233], Lam et al [234], Neimitz et al [235], and Shen et al [236]. All experimental results showed that deeply cracked, bending loaded standard specimens result in lower J-R curves, and shallow cracked, predominantly tensile loaded nonstandard specimens lead to higher J-R curves, with the plane strain initiation toughness J Ic being nearly independent of these specimen geometry and loading mode effects.…”
Section: Experimental Observations On Fracture Constraint Effectsupporting
confidence: 54%
“…Since the RKR model is not applicable to growing cracks, a new methodology has been developed to relate a constant value of Q or A 2 to each resistance curve. The first author and his coworkers [234,271,279,281,290,291] have proposed a unique technique for correcting constraint effect on J-R curves using the parameter Q or A 2 . By assuming an analytic power-law function, a family of constraint-dependent J-R curves can be constructed for ductile crack growth, in conjunction with use of at least three typical experimental J-R curve data and numerical results of the constraint parameter determined at the loading level of initiation toughness.…”
Section: Constraint Correction Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crack growth criteria development -CTOD/CTOA The crack growth resistance (J-R) curves for A285 carbon steel (the material of construction for Type I and II waste tanks) were determined using bend specimens with various a/W (crack length to specimen width) ratios. These geometry dependent J-R curves can be expressed as a function of a crack tip constraint parameter [2]. In this subtask, the fracture testing in Ref.…”
Section: Fracture Methodology Assessmentmentioning
confidence: 99%
“…This trend can be qualitatively demonstrated. Since the J-R curves are crack-tip-constraint dependent [2], the CTOD/CTOA fracture criteria must also be a function of constraint. Without the initially higher values of CTOD/CTOA, the fracture testing data will be underestimated [3].…”
Section: Fracture Methodology Assessmentmentioning
confidence: 99%